Antibiotics and Antivirals in COVID-19: Clinical Outcomes: Pengaruh Obat Antibiotik & Antivirus pada Pasien COVID-19: Pedoman Tatalaksana Edisi 3 (2020) - Godeliva Adriani Hendra; Monika Turnip; FX. Haryanto Susanto (Academia Open, 2023)
The clinical manifestations of COVID-19 disease are mainly caused by an irregular host response associated with excessive expression of inflammatory markers. Patients with mild, moderate, and severe symptoms of COVID-19 with or without comorbidities use a combination of antiviral drugs and antibiotics. This study aimed to determine the relationship between the use of antiviral drugs and antibiotics on the clinical outcomes of COVID-19 patients. The research design used a cross-sectional study with retrospective data collection. The inclusion criteria were COVID-19 patients hospitalized at Panti Waluya Sawahan Malang Hospital with or without comorbidities, positive RT-PCR results, and receiving antibiotic and antiviral therapy. The clinical outcome is a patient improvement if the length of stay is 14 days, and the patient worsens if it is >14 days. There is no relationship between antibiotics and antiviral drugs on the clinical outcomes of COVID-19 patients (p>0,05). Highlights: Excessive expression of inflammatory markers contributes to the clinical manifestations of COVID-19. Combination therapy of antiviral drugs and antibiotics is commonly used for COVID-19 patients. The study found no significant relationship between the use of antibiotics and antiviral drugs and the clinical outcomes of COVID-19 patients Keywords: antibiotics, antiviruses, COVID-19, clinical improvement, clinical deterioration